Rejecting Cain’s Offering but Accepting Abel’s: Exegetical and Theological Study on Genesis 4:3-5 - Blasius Abin (Peneliti.net, 2022)
Two brothers have two different vocations: ”Abel was a keeper of flocks, but Cain was a tiller of the ground” (Gen. 4:2, NKJV). Each of them naturally presented offerings to the true God from that which they had to offer. The issue is that, God looked with favor on Abel’s minhah but not on Cain’s. Scholars have given their interpretations to investigate the rationale of God’s disapproval of Cain’s offering. Most interpretations have suggested that God’s approval and disapproval are due to the nature of offering. This presupposition is not supported by the literal context of the story. Through literary study, exegetical, and theological investigations of the text, this study conclude that God distinguishes the offering and the motive of the offerer. That is, there is a causal connection between the motive and the offering of human beings. Cain’s motive was explicated through his resentment and annihilation of his brother, Abel. The implication is obvious; the offering stands as a visible representation of the human motive. Hence, the quality of Abel and Cain’s offerings were derived from their motives. This capitalizes the basis of God’s approval and disapproval of the offering. To sum, the rationale of God’s assessment to the offering of Cain and Abel is based on the motive and character of the offerer